The Impact of Automated Corrective Feedback on EFL Learners' Writing Improvement The Case of Second Year EFL Students at Mohamed Cherif Messaadia University, Souk-Ahras - Rayan BAHLOUL (My University, 2022)
Abstract The adoption of online teaching during the Covid 19 pandemic affected in many ways the teaching process in general, and the teaching of the writing skill in particular, especially, in the phase of providing the teachers' feedback to their students' writings, which is considered as a key part in the writing process. In this case, Automated Corrective Feedback is supposed to be an alternative to teachers' feedback, which may guide the students and help them to ameliorate their writings. However, students' and teachers' attitudes and reactions towards this type of feedback may vary. Therefore, this study aims to investigate the teachers' and students' attitudes regarding the use of automated corrective feedback programs. To meet the aim of the study, an interview was conducted with EFL teachers and a questionnaire was submitted to second year students from the department of English at Mohamed Cherif Messaadia University. The collected data were analyzed both quantitatively and qualitatively then they were discussed and interpreted. Therefore, according to the findings, it was recognized that both teachers and students insisted on the necessity of using ACF as a relevant tool for helping students to become good writers. Furthermore, the results revealed that ACF can overcome the students writing problems. So, the obtained findings confirm the proposed hypothesis and give insights to a number of suggestions that can help the students to develop their writing skill.